Implementation science: What is it and why should I care?. (January 2020) - Bauer, Mark S.; Kirchner, JoAnn
Highlights: Establishing effectiveness of an innovation does not guarantee its uptake into routine usage. Innovation uptake depends largely on contextual factors, not just innovation effectiveness. Implementation science addresses such contextual barriers and facilitators to enhance innovation uptake. Abstract: Centuries of experience make it clear that establishing the effectiveness of a clinical innovation is not sufficient to guarantee its uptake into routine use. The relatively new field of implementation science has developed to enhance the uptake of evidence-based practices and thereby increase their public health impact. Implementation science shares many characteristics, and the rigorous approach, of clinical research. However, it is distinct in that it attends to factors in addition to the effectiveness of the clinical innovation itself, to include identifying and addressing barriers and facilitators to the uptake of evidence-based clinical innovations. This article reviews the definition, history, and scope of implementation science, and places the field within the broader enterprise of biomedical research. It also provides an overview of this Special Issue of Psychiatry Research, which introduces the principles and methods of implementation science to mental health researchers.